THE IMPACT OF DIGITAL FRAUD RISK, SECURITY, AND SHARIA TRUST ON SHOPEE USERS (CASE STUDY: SHOPEE USERS IN MEDAN) - Aini, Khadijah Nur; Nurbaiti, Nurbaiti; Silalahi, Purnama Ramadani (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study was conducted to examine the influence of digital fraud risk, security, and Sharia trust on people’s decisions to use the Shopee app in Medan. The method used was a quantitative approach with an associative research design. The study sample consisted of 100 respondents selected using purposive sampling. Data collection was carried out through the distribution of questionnaires, which were then analyzed using multiple linear regression supported by t-tests, F-tests, and the coefficient of determination (R²). The results of the analysis indicate that the risk of digital fraud, security, and Sharia trust have a significant influence both partially and simultaneously on the decision to use Shopee, as indicated by a significance level of < 0.05. Furthermore, an R² value of 0.660 indicates that 66% of the variation in the decision to use Shopee can be explained by these three variables. Thus, the decision to use Shopee is influenced by the risk of digital fraud, security, and Sharia trust. Keywords: Risk of Digital Fraud, Security, Sharia Trust, Shopee Users